2020
DOI: 10.1016/s2214-109x(20)30227-8
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of post-treatment follow-up examinations and secondary prevention of tuberculosis in a high-incidence setting: a model-based analysis

Abstract: Background In settings of high tuberculosis incidence, previously treated individuals remain at high risk of recurrent tuberculosis and contribute substantially to overall disease burden. Whether tuberculosis case finding and preventive interventions among previously treated people are cost-effective has not been established. We aimed to estimate costs and health benefits of annual post-treatment follow-up examinations and secondary preventive therapy for tuberculosis in a tuberculosis-endemic setting.Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…126,128 Alternatively, if an innovative modeling approach is being used, this approach might be related to the outcomes needed for decision makers or how the chosen model structure better reflects disease natural history, current treatment practice, and efficacy and safety compared with previous models in the disease area. The use of an innovative approach might also be related to the extent Example of Item 15: Currency, price date and conversion 124 "We estimated the costs for the base-case and intervention scenarios in 2018 US dollars, adopting a South African health-care system perspective (table 1). Average costs reflect 2018 estimates for tuberculosis health-care and diagnostic services in Cape Town that were obtained through review of the published literature and the official price list of the National Health Laboratory Service, South Africa.…”
Section: Explanation Analyses Based On Preference-based Outcomementioning
confidence: 99%
“…126,128 Alternatively, if an innovative modeling approach is being used, this approach might be related to the outcomes needed for decision makers or how the chosen model structure better reflects disease natural history, current treatment practice, and efficacy and safety compared with previous models in the disease area. The use of an innovative approach might also be related to the extent Example of Item 15: Currency, price date and conversion 124 "We estimated the costs for the base-case and intervention scenarios in 2018 US dollars, adopting a South African health-care system perspective (table 1). Average costs reflect 2018 estimates for tuberculosis health-care and diagnostic services in Cape Town that were obtained through review of the published literature and the official price list of the National Health Laboratory Service, South Africa.…”
Section: Explanation Analyses Based On Preference-based Outcomementioning
confidence: 99%
“…Other evidence shows the positive impact of post-TB rehabilitation on lung health [48]. A recent study from a high incidence TB/HIV setting in South Africa demonstrated that a post-TB follow-up strategy without, or preferred with, post-TB preventative therapy could be a cost-effective approach to improve TB control [49].…”
Section: Evolution Of New Aspects On Treatment Outcome Definitions (With Focus On Research and Programmatic Management)mentioning
confidence: 99%
“…Individuals who have received the previous treatment are still at high risk of recurrent TB. Follow-up after the treatment and secondary preventive treatment can accelerate the decline in the incidence of TB, and follow-up after the treatment is also very important (8). In addition, innovations in patient-centered strategies and advances in testing and treatment are also critical to ending the TB epidemic (9,10).…”
Section: Introductionmentioning
confidence: 99%